Peninsular memory of a legacy to XXI Century: Francisco Suárez (1617-2017) - Lázaro Pulido, Manuel; Zorroza, Mª Idoya (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
This paper introduce the different scientific activities (congresses, international conferences and meetings, publications) that have been prepared and that are being organized between 2017 and 2018, in occasion of the fourth centenary of the death of Francisco Suarez. These activities show the intellectual wealth of the Suarezian thought, not only because of its historical relevance, but also as a thought for rethinking our contemporary time.